(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Cultural history is one of the less frequented historiographical fields in the lines of research that deal with Michoacan. This essay has the purpose of exploring some of the most representative aspects in this field in the entity, for the initial decades of the independent period. From a generic approach on how the civic pantheon of moder- nity was set up, we also present the circumstances and historical conditions under which the first steps were taken in that regard. Largely the actions of this type in the entity, departed from the attention and imitation of the measures undertaken by the general powers, to vindicate the main heroes of the war of independence. However, in the case of Michoacan proposals of heroization of figures such as Matamoros, Villalongin, Garcia Obeso and even Jose Maria Morelos, found strong resistance from members of the political class responsible to take decisions to institutionalize them or not, therefore they had to deal with, in addition to the interference of the Church, prejudices and resentments, explainable in good measured by the then recent performance in life of these characters